2016
DOI: 10.1016/j.ijhydene.2016.05.285
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal assisted morphology designed MoS 2 material as alternative cathode catalyst for PEM electrolyser application

Abstract: Available online xxxKeywords: Hydrothermal method MoS 2 Nano shapes HER PEM electrolyser Hydrogen production a b s t r a c t In this work, we developed a simple and cost-effective hydrothermal route to regulate the formation of molybdenum disulfide (MoS 2 ) in different morphologies, like, nano-sheet, nano-capsule and nano-flake structure by controlling the reaction temperature and sulphur precursor employed. Such a fine tuning of different morphologies yields a leverage to obtain novel shapes with high surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 51 publications
(28 reference statements)
2
18
0
Order By: Relevance
“…[ 19–24 ] Only few studies report a full cell performance analysis of PEMWE membrane electrode assemblies (MEAs) using PGM‐free HER catalysts. [ 19,25–29 ] To our knowledge, the highest performances of a PEMWE cell using a non‐noble metal HER catalyst was obtained by Jaramilo's group, who tested and compared three MoS/MoP on carbon black (CB) catalysts. [ 19 ] Best performance was achieved for MoP|S‐CB, which reached current densities of up to ≈1.2 A cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 19–24 ] Only few studies report a full cell performance analysis of PEMWE membrane electrode assemblies (MEAs) using PGM‐free HER catalysts. [ 19,25–29 ] To our knowledge, the highest performances of a PEMWE cell using a non‐noble metal HER catalyst was obtained by Jaramilo's group, who tested and compared three MoS/MoP on carbon black (CB) catalysts. [ 19 ] Best performance was achieved for MoP|S‐CB, which reached current densities of up to ≈1.2 A cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…In early 2016 Kumar et al reported that a cell with a MoS 2 nanocapsule cathode maintained a current density of approximately 60 mA/cm 2 for 200 h at 2.0 V [106]. The cell consisted of a Nafion membrane and IrO 2 anode.…”
Section: Molybdenum Sulfide Mosmentioning
confidence: 99%
“…Currently, to the best of our knowledge, despite the impressive catalytic activity claimed and experimentally demonstrated for the TMDs, there are no commercial water electrolyzers based on these materials. In fact, only some proof‐of‐concept electrolyzers have been reported using, for example, MoS 2 , [ 46–49 ] RuTe 2 , [ 50 ] FeS 2 [ 51 ] and NbS 2 [ 52 ] as cathode materials. Such aspects indicate the need to systematically validate the use of TMDs as HER‐EC into practical electrolyzers to advance the technologies for the electrochemical hydrogen production.…”
Section: Introductionmentioning
confidence: 99%